Pertanggung Jawaban Pidana Terhadap Pihak Perantara Dalam Kasus Hilangnya Kendaraan Pada Usaha Rental Mobil - Muhammad, Muhammad; Rahmah, Siti; Aguswandi, Putra (Islamic Family Law Department, Sharia Faculty, Stai Syekh Abdur Rauf, Aceh Singkil, 2025)
This study aims to examine the criminal liability of intermediaries in cases of vehicle loss in car rental businesses based on the perspective of Indonesian criminal law. The study uses a normative legal method with a statute approach and an analytical approach. The data used comes from primary legal materials in the form of laws and regulations, secondary legal materials in the form of books, journals, and scientific articles, and tertiary legal materials such as legal dictionaries and encyclopedias. The data collection technique is carried out through literature studies, while data analysis uses a descriptive-analytical method. The results of the study indicate that the criminal liability of intermediaries can be classified as a crime of embezzlement (Article 372 of the Criminal Code), fraud (Article 378 of the Criminal Code), or theft (Article 362 of the Criminal Code), depending on the modus operandi used. Factors determining liability include the role and function of the intermediary, the element of intent, and the causal relationship between the act and the consequence. In judicial practice, proving subjective and objective elements is often an obstacle. This study concludes that the criminal liability of intermediaries is significantly influenced by their level of involvement and the fulfillment of the elements of the crime charged. The study recommends the need for more comprehensive regulations, improved identity verification, and strengthened coordination between law enforcement and rental businesses to prevent and combat crime in this sector. [Penelitian ini bertujuan untuk mengkaji pertanggungjawaban pidana pihak perantara dalam kasus hilangnya kendaraan pada usaha rental mobil berdasarkan perspektif hukum pidana Indonesia. Penelitian menggunakan metode hukum normatif dengan pendekatan perundang-undangan (statute approach) dan analisis (analytical approach). Data yang digunakan berasal dari bahan hukum primer berupa peraturan perundang-undangan, bahan hukum sekunder berupa buku, jurnal, dan artikel ilmiah, serta bahan hukum tersier seperti kamus hukum dan ensiklopedia. Teknik pengumpulan data dilakukan melalui studi kepustakaan, sedangkan analisis data menggunakan metode deskriptif-analitis. Hasil penelitian menunjukkan bahwa pertanggungjawaban pidana pihak perantara dapat dikualifikasikan sebagai tindak pidana penggelapan (Pasal 372 KUHP), penipuan (Pasal 378 KUHP), atau pencurian (Pasal 362 KUHP), tergantung pada modus operandi yang dilakukan. Faktor penentu pertanggungjawaban meliputi peran dan fungsi perantara, unsur kesengajaan, serta hubungan kausalitas antara perbuatan dan akibat. Dalam praktik peradilan, pembuktian unsur subjektif dan objektif sering menjadi kendala. Penelitian ini menyimpulkan bahwa pertanggungjawaban pidana perantara sangat dipengaruhi oleh tingkat keterlibatan dan terpenuhinya unsur-unsur tindak pidana yang didakwakan. Saran penelitian adalah perlunya regulasi yang lebih komprehensif, peningkatan verifikasi identitas, serta penguatan koordinasi antara aparat penegak hukum dan pelaku usaha rental untuk mencegah dan menanggulangi tindak pidana di sektor ini.]